PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET PADA STIKOM DINAMIKA BANGSA JAMBI (Studi Kasus: Penjualan dan Disposal Aset Tetap) - Maria Rosario Borroek (LPPM STIKOM Dinamika Bangsa, 2014)
The asset management of STIKOM Dinamika Bangsa Jambi is have not optimal yet, one of several ways to optimize its management is by the use of information systems. The assets that were not optimal in its function will then usually be carried out or removed. This research produced a prototype system that describes the functional of selling and removing assets at STIKOM Dinamika Bangsa Jambi. The model of system development used in this research is the Unified Modeling Language i.e. use case diagrams, class diagrams and activity. Keywords : Design, Asset Management, UML